2010 12th International Conference on Frontiers in Handwriting Recognition 2010
DOI: 10.1109/icfhr.2010.82
|View full text |Cite
|
Sign up to set email alerts
|

Ontology-Based Information Extraction from Handwritten Documents

Abstract: In this paper we introduce a new layer for the task of handwriting recognition. We add semantic information by means of ontologies. The task of our recognizer therefore is not only to recognize the ASCII transcription of the handwritten document, but also to identify the semantic concepts which appear in the text. This task is called ontology-based information extraction (OBIE), which has been applied to electronic documents recently. OBIE methods first segment the text into tokens, then identify their values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…j ) is the belief value of the j-th instance in the path. In [6] experiments of ontology-based information extraction (OBIE) have shown that the proposed extension performs better than a simple approach which just feeds the output of the recognizer as an input to the OBIE system. Furthermore, using the ontology instances to alter the recognition lexicon increased the f-measure up to 69.67 % which is close to the performance on electronic text which is already available in ASCII.…”
Section: Ontology-based Information Extraction Frommentioning
confidence: 99%
“…j ) is the belief value of the j-th instance in the path. In [6] experiments of ontology-based information extraction (OBIE) have shown that the proposed extension performs better than a simple approach which just feeds the output of the recognizer as an input to the OBIE system. Furthermore, using the ontology instances to alter the recognition lexicon increased the f-measure up to 69.67 % which is close to the performance on electronic text which is already available in ASCII.…”
Section: Ontology-based Information Extraction Frommentioning
confidence: 99%